Life Course Transitions and Changes in Alcohol Consumption Among Older Irish Adults: Results From The Irish Longitudinal Study on Ageing (TILDA). (October 2019) - Holton, Alice; Boland, Fiona; Gallagher, Paul; Fahey, Tom; Kenny, Roseanne; Cousins, Gráinne
Objective: The objective of this study was to determine whether trajectories of older adults' alcohol consumption are influenced by the following life course transitions, relationship status, employment status, and self-rated health.Method: Volume and frequency of drinking were harmonized across first three waves of The Irish Longitudinal Study on Ageing (TILDA; N = 4, 295). Multilevel regression models were used to model frequency, average weekly consumption, and heavy episodic drinking.Results: Men and women drank more frequently over time, with frequency decreasing with age for women. Average weekly consumption decreased over time and with increasing age. Transitions in self-rated health, particularly those reflecting poorer health, were associated with lower frequency and weekly consumption. Heavy episodic drinking decreased with age. Men who were retired across all waves were more likely to engage in heavy episodic drinking at baseline.Discussion: Despite the decline in average weekly consumption and heavy episodic drinking, the observed quantities consumed and the increase in frequency of consumption suggest that older Irish adults remain vulnerable to alcohol-related harms.